1985
DOI: 10.1172/jci112036
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunostimulatory dendritic cells in the synovial effusions of patients with rheumatoid arthritis.

Abstract: Dendritic cells in the circulation are leukocytes that are rich in Ia antigens and that actively stimulate T cell replication. We have identified dendritic cells in the joint effusions of patients with rheumatoid arthritis. By phase-contrast and immunofluorescence microscopy, synovial mononuclear cells contained 1-5% dendritic profiles that were rich in HLA-DR and DQ, had small amounts of C3bi receptor, and lacked a battery of monocyte and lymphocyte markers. These dendritic cells could be enriched to 604-0% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(50 citation statements)
references
References 46 publications
1
49
0
Order By: Relevance
“…DC have been identified in rheumatoid ST and SF by several groups over the last 15 years, and elucidation of their derivation, function, and potential role in the pathogenesis of the disease is increasingly better understood [1,2,[9][10][11][12][13][14][15][16][17][18][19][20]. Myeloid DC can be identified and freshly purified from normal or RA peripheral blood (PB), RA SF, or ST cell suspensions through the use of a combination of myeloid markers, and it is therefore possible to directly compare the phenotype and function of PB and SF DC.…”
Section: In Rheumatoid Synoviummentioning
confidence: 99%
See 1 more Smart Citation
“…DC have been identified in rheumatoid ST and SF by several groups over the last 15 years, and elucidation of their derivation, function, and potential role in the pathogenesis of the disease is increasingly better understood [1,2,[9][10][11][12][13][14][15][16][17][18][19][20]. Myeloid DC can be identified and freshly purified from normal or RA peripheral blood (PB), RA SF, or ST cell suspensions through the use of a combination of myeloid markers, and it is therefore possible to directly compare the phenotype and function of PB and SF DC.…”
Section: In Rheumatoid Synoviummentioning
confidence: 99%
“…SF DC and PB DC stimulated resting allogeneic T cells with equivalent efficacy, and more efficiently than SF monocytes. However, SF DC were markedly more efficient simulators of autologous T cells in the absence of exogenous antigen (autologous MLR) [11,16,17,21]. Many investigators have been able to demonstrate the presence of autoreactive T cells in RA, both by the autologous MLR and by deriving clones from PB, SF, or ST, and it appears likely that autoreactive T cells are expanded in the circulation of these patients and their unaffected first degree relatives [22][23][24][25].…”
Section: In Rheumatoid Synoviummentioning
confidence: 99%
“…The purity of dendritic cell-enriched cell populations thus obtained varied from 50% to 80%, as estimated on the basis of characteristic dendritic cell morphology and strong HLA-DQ expression. For some experiments, further dendritic cell enrichment was accomplished by treating the cells with anti-CD3 (Becton Dickinson, Mountain View, CA) and 63D3 (Bethesda Research Laboratories, Gaithersburg, MD) monoclonal antibodies and rabbit complement (Cedarlane, Hornby, Ontario, Canada) as previously described (21).…”
Section: Methodsmentioning
confidence: 99%
“…Unlike intimal macrophages, the precise origin of type B synoviocytes remains unclear, although they are thought to arise from the sublining tissue or other support structures of a joint (Firestein,1996). On the other hand, a number of studies have shown that peripheral blood dendritic cells (DC) accumulate in the synovium, where they undergo phenotypic and functional differentiation in situ (Zvaifler et al,1985;Thomas et al,1994). It has been also shown that synovial DC gradually lose their dinstinct morphologic appearance and become indistinguishable from fibroblasts in vitro (Hendler et al,1985).…”
Section: Evidence For Recruitment Of Cells From Systemic Circulation mentioning
confidence: 99%